3-Carboxamide oxindoles as 1, 3-C, N-bisnucleophiles for the highly diastereoselective synthesis of CF3-containing spiro-δ-lactam oxindoles featuring acyl at the ortho-position of spiro carbon atom. (26th October 2021) - Zhao, Hongcai; Zhang, Zhengbing; Lu, Wenhua; Han, Pan; Wang, Wei; Jing, Linhai
Graphical abstract: Abstract: A simple and efficient strategy has been established for the synthesis of δ-lactam fused oxindoles via the Michael/ N -hemiketalization cascade reaction of 3-carboxamide oxindoles and α, β-unsaturated trifluoromethyl ketones. A wide range of structurally novel CF3 -containing spiro-δ-lactam oxindoles featuring acyl at the ortho -position of spiro carbon atoms were obtained in moderate to good yields with excellent diastereoselectivities under mild conditions. This work represents the first example of a systematic study of 3-carboxamide oxindoles as 1, 3-C, N bisnucleophiles.